ANALISIS YURIDIS DISPARITAS PEMENUHAN HAK RESTITUSI ANAK KORBAN PERSETUBUHAN DALAM PUTUSAN HAKIM PERKARA PIDANA KHUSUS - Putri, Chelsy Trisya Salsabilah; Imran, Suwitno Yutye; Mustika, Waode (CV Widina Media Utama, 2026)
The prevalence of sexual violence against children in Indonesia has not been matched by law enforcement that prioritizes the victims, particularly regarding their right to material recovery through restitution mechanisms. This study aims to conduct an in-depth analysis of the determining factors underlying the disparity in judicial rulings regarding the fulfillment of restitution rights for child victims of sexual intercourse. Using a normative legal research method with legislative, case-based, and conceptual approaches, this study examines the ratio decidendi of three different judicial jurisdictions: Judgment No. 267/Pid.Sus/2024/PN Gto, Judgment No. 26/Pid.Sus/2023/PN Tbn, and Judgment No. 35/Pid.Sus/2022/PN Jnp. The results of the study reveal massive inconsistencies in the fulfillment of children’s rights to restitution, influenced by four main factors: the passive role of the public prosecutor as dominus litis in filing and overseeing restitution documents; the antinomic tension between formal legal certainty and substantive justice; technical obstacles in proving immaterial damages; and the low degree of internalization of the principle of the best interests of the child among judges, as reflected in the total denial of restitution in the case of a 14-month-old toddler victim in Jeneponto. The study’s conclusions affirm that the main problem in ensuring restitution lies not in the absence of legal norms, but rather in the lack of consistency in implementation due to a law enforcement paradigm that remains offender-oriented. A regulatory overhaul is needed to grant judges ex officio authority to order minimum restitution in order to ensure the fair and optimal restoration of the rights of child victims. ABSTRAKMaraknya kekerasan seksual pada anak di Indonesia belum diimbangi dengan penegakan hukum yang berpihak pada korban, terutama terkait hak pemulihan material melalui mekanisme restitusi. Penelitian ini bertujuan untuk menganalisis secara mendalam faktor faktor determinan yang melatarbelakangi terjadinya disparitas putusan hakim dalam pemenuhan hak restitusi anak korban persetubuhan. Menggunakan metode penelitian hukum yuridis normatif dengan pendekatan perundang-undangan, pendekatan kasus, dan pendekatan konseptual, penelitian ini mengkaji ratio decidendi dari tiga yurisdiksi peradilan yang berbeda, yaitu Putusan Nomor 267/Pid.Sus/2024/PN Gto, Putusan Nomor 26/Pid.Sus/2023/PN Tbn, dan Putusan Nomor 35/Pid.Sus/2022/PN Jnp. Hasil penelitian menunjukkan adanya inkonsistensi masif dalam pemenuhan hak restitusi anak yang dipengaruhi oleh empat faktor utama: pasifnya peran penuntut umum sebagai dominus litis dalam mengajukan dan mengawal dokumen restitusi; ketegangan antinomi nilai antara kepastian hukum formal dan keadilan substantif; hambatan teknis pembuktian kerugian immaterial; serta rendahnya derajat internalisasi prinsip kepentingan terbaik bagi anak (the best interest of the child) di sanubari hakim, tecermin dari penolakan total restitusi pada kasus korban balita berusia 14 bulan di Jeneponto. Kesimpulan penelitian menegaskan bahwa problem utama pemenuhan restitusi bukan terletak pada ketiadaan norma hukum, melainkan pada lemahnya konsistensi implementasi akibat paradigma penegak hukum yang masih bersifat offender oriented. Diperlukan rekonstruksi regulasi yang memberikan wewenang ex officio kepada hakim untuk menetapkan restitusi minimal demi menjamin pemulihan hak korban anak secara adil dan optimal.